2006
DOI: 10.4049/jimmunol.176.4.2407
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Protein Kinase Cε in the Negative Regulation of Akt Activation Stimulated by Granulocyte Colony-Stimulating Factor

Abstract: Stimulation of cells with G-CSF activates multiple signaling cascades, including the serine/threonine kinase Akt pathway. We show in this study that G-CSF-induced activation of Akt in myeloid 32D was specifically inhibited by treatment with PMA, a protein kinase C (PKC) activator. PMA treatment also rapidly attenuated sustained Akt activation mediated by a carboxy truncated G-CSF receptor, expressed in patients with acute myeloid leukemia evolving from severe congenital neutropenia. The inhibitory effect of PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 56 publications
3
13
1
Order By: Relevance
“…Contrary to the data cited above, there are some reports that suggest that PKC negatively regulates Akt function [116][117][118][119][120][121], and this was associated with increased apoptosis. Suppression of Akt phosphorylation in response to PKC activators or adenoviral expression of PKCε has been shown to occur via PP2A [117,119].…”
Section: Pkcε: Akting In Concert To Promote Survivalcontrasting
confidence: 62%
See 1 more Smart Citation
“…Contrary to the data cited above, there are some reports that suggest that PKC negatively regulates Akt function [116][117][118][119][120][121], and this was associated with increased apoptosis. Suppression of Akt phosphorylation in response to PKC activators or adenoviral expression of PKCε has been shown to occur via PP2A [117,119].…”
Section: Pkcε: Akting In Concert To Promote Survivalcontrasting
confidence: 62%
“…Moreover, TPA co-treatment diminished the capacity of IGF to protect against UVC-induced cell death, while PKC inhibitors enhanced cell survival [119]. Similarly, in myeloid cell lines, Liu and colleagues showed that wild-type or constitutively-active PKCε attenuated cell proliferation stimulated by granulocyte colony-stimulating factor [120]. This inhibitory effect was associated with a decrease in Akt phosphorylation.…”
Section: Pkcε: Akting In Concert To Promote Survivalmentioning
confidence: 97%
“…PI3K products have been shown to activate nPKCε in vitro (35), and IFN␥-induced activation of nPKCε in mesangial cells is inhibited by PI3K inhibitor (7). However, nPKCε and PMA have been shown to inhibit granulocyte colony-stimulating factor-induced activation of PKB in myeloid 32D cells (21), and activation of nPKC␦ and nPKCε results in inhibition of PKB in mouse keratinocytes (20). Thus whether nPKCε regulates PKB activity or PI3K regulates nPKCε activity appears to be dependent on cell type and stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…nPKCε has been shown to inhibit PKB in mouse keratinocytes (20) and myeloid 32D cells (21). Thus we determined whether TLC induced inhibition of PKB in HuH-NTCP cells is mediated via PKCε.…”
Section: Tlc Does Not Inhibit Ntcp Translocation and Competitively Inmentioning
confidence: 99%
See 1 more Smart Citation